Distributed optimal tie-line power flow control for multiple interconnected AC microgrids - Liu, Yun (2019)
In a multi-microgrid system (MMG), the microgrids (MGs) are normally managed by independent operators. Distributed energy trading/scheduling schemes via interactions of these MG operators have been extensively investigated. How to coordinate these MGs to implement the acquired optimal schedule in the real time under constant load fluctuation while guaranteeing operational stability is seldom reported. Due to the intrinsic advantages of scalability, robustness, and fast response in comparison to the centralized scheme, a multi-agent based distributed optimal tie-line power flow control strategy is proposed to achieve this objective, which is facilitated by a regional communication network overlapping each MG and distributed sensors monitoring the tie-line power flows. When the MMG is operated in the grid-connected mode, the proposed scheme can maintain the scheduled tie-line power flows among the MGs in the presence of any disturbance by adjusting the real-time power outputs of the distributed energy resources proportionally. When the MMG is islanded, frequency recovery can be further achieved via a local frequency feedback mechanism. Convergence of the proposed approach is analytically proved. Simulation results in a four-MG system modified from the IEEE 34-bus test feeder system validate the effectiveness and efficiency of the proposed approach in both grid-connected and islanded modes.